Radiosensitivity of three tomato varieties (Solanum lycopersicum L.) irradiated with Cobalt-60 gamma rays - Jaén Villarreal, Jorge Enrique (2024)
Introduction. Tomato (Solanum lycopersicum L.) is considered one of the most important crops in the world. Genetic improvement of tomatoes has employed different methods to generate variability, and mutation the induction of mutations is one of the techniques used to obtaining improved varieties. The first step in using this tool is studying radiosensitivity to determine the irradiation dose to be used. Objective. To determine the radiosensitivity and the dose of cobalt-60 gamma rays to be used in three tomato varieties. Materials and methods. This research was conducted in January 2020 at the Instituto Nacional de Ciencias Agrícolas of Cuba. Seeds of three tomato varieties were irradiated with cobalt-60 gamma rays, with doses ranging from 100 Gy to 900 Gy, at intervals of 100 Gy; an unirradiated control was also used. The percentage of germination, plant height, and seedling survival were evaluated. Results. It was observed that higher irradiation dose reduced germination, survival, and plant height. The IDIAP T-7 and IDIAP T-9 varieties reduced germination at a dose of 400 Gy, while the DINA RPs cultivar reduced germination at 300 Gy. Genotypes showed survival values below 50 % at a dose of 800 Gy. Height reduction began at doses of 200 Gy for IDIAP T-7, 300 Gy for DINA RPs, and 400 Gy for IDIAP T-9. Conclusion. The DL-50 doses were identified as 692, 588, and 630 Gy, and the GR-50 doses were 407, 467, and 380 Gy for the IDIAP T-7, IDIAP T-9, and DINA RPs varieties, respectively. The GR-50 dose of each variety was selected for the mutation breeding program.